Analisis Kesulitan Siswa Kelas IV SD dalam Membedakan Konsep IPA dan IPS pada Pembelajaran IPAS SDN 064966 - Fenny Rizky Amelia; Icha Parista; Hizkia Adventy Saragih; Gita Rismayani; Aurora Novena Simamora (CV.ITTC INDONESIA, 2025)
This study aims to analyze the difficulties of grade IV students in distinguishing the concepts of Natural Science (IPA) and Social Science (IPS) in learning Natural and Social Sciences (IPAS) at SDN 064966. A descriptive qualitative approach was used to explore students' experiences and teachers' learning strategies in the context of Merdeka Curriculum. Data were obtained through semi-structured interviews, classroom observations, and closed and open questionnaires distributed to 16 students. The results showed that the integration of science and social studies in IPAS caused conceptual confusion, characterized by students' misconceptions in categorizing materials, such as considering history topics as part of science. Students also showed a high need for visual media, practical learning, and a more collaborative approach. Less explicit learning in distinguishing the characteristics of each discipline reinforces this difficulty. This research recommends the use of visual symbols, conceptual tagging and contextual learning strategies that emphasize the distinction between science and social studies clearly. With these approaches, it is expected that students' understanding of concepts will improve and IPAS learning will be more effective.